Massive Ovarian Edema in a Girl with Hemoglobin SC Disease - Eric Johannesen; Van Nguyen (Hindawi Limited, 2018)
Massive ovarian edema is a benign tumor like lesion of the ovary. The widely accepted mechanism is disruption of vascular drainage resulting in accumulation of fluid within the stroma and enlargement of the ovary. We report a case of massive ovarian edema in a teenage girl with hemoglobin SC disease. A 16-year-old female with hemoglobin SC disease was admitted with right lower quadrant pain. An ultrasound and CT scan showed a large, heterogeneous solid, and cystic pelvic mass. Due to the size and the possibility of malignancy, the patient underwent a salpingo-oophorectomy. The mass was an 8.3 cm hemorrhagic cyst with some solid areas. Histologic exam showed diffuse edema with scattered entrapped follicles and a narrow rim of normal appearing ovarian stroma. Dilated and occluded capillaries were seen along with hemorrhage and sickled red blood cells but no necrosis was identified. These histologic features were consistent with massive ovarian edema. Massive ovarian edema is thought to be caused by disturbance of the vascular outflow resulting in fluid buildup in the stroma. It is most often attributed to intermittent ovarian torsion that disrupts capillary and venous flow, but arterial flow is maintained. Rare cases of massive ovarian edema caused by tumor emboli or external compression by tumors have been reported, but this is the first case of a patient with hemoglobin SC disease developing vasoocclusions resulting in this lesion.